Compact parylene‐c‐coated flexible antenna for WLAN and upper‐band UWB applications. Issue 24 (1st November 2014) - Qiu, Yijie; Jung, Yei Hwan; Lee, Subin; Shih, Ting‐Yen; Lee, Juhwan; Xu, Yue Hang; Xu, Ruimin; Lin, Weigan; Behdad, Nader; Ma, Zhenqiang
Abstract : A compact broadband flexible antenna is proposed for applications in wireless local area network (WLAN) and upper ultra‐wideband (UWB) systems, which can operate in the bandwidths of 2.4–2.484 GHz and 3.5–10.6 GHz with a reflection coefficient of <−10 dB. The presented antenna coated with bio‐compatible ultra‐thin parylene‐c is fabricated on a thin polyimide substrate with a thickness of 127 μm. The characteristics of the proposed antenna are measured under bending and flat conditions. The measured results showed that the antenna is suitable for integration with flexible electronic devices.